Hubungan Self Efficacy dengan Burnout Pengasuhan Pada Ibu Bekerja yang Memiliki Anak Usia Dini (0-6 Tahun) - Sugiana Sugiana; Pitri Yuliyani (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2026)
The increasing demands of multiple roles on working mothers who have young children have the potential to trigger parenting burnout due to ongoing pressure. This study aims to determine the relationship between self-efficacy and parenting burnout in working mothers who have children aged 0-6 years. The research method uses a non-experimental quantitative approach. The population in this study were working mothers who had children aged 0-6 years) in Beji Krajan Village, Semarang Regency. The total sample was 95 working mothers who were determined through random sampling techniques using the Slovin formula. Caregiving burnout can be measured through the aspects of physical fatigue, mental fatigue, emotional exhaustion, depersonalization, and decreased personal achievement. Meanwhile, the self-efficacy aspect can be measured through the aspects of magnitude, generality and strength. The results of data analysis in this study show a correlation coefficient of -0.716, with p = 0.00, which indicates that the relationship between the two variables is significantly negative. Based on data analysis, it can be concluded that there is a significant negative relationship between self-efficacy and parenting burnout in working mothers who have children aged 0-6 years, which means that if self-efficacy is high, then parenting burnout in working mothers who have children aged 0-6 years) decreases. On the other hand, the lower the self-efficacy, the higher the parenting burnout for working mothers who have children aged 0-6 years.